Changes in Adolescents' Premarital Sex Attitudes After Reproductive Health Education - Amanda Ayu Ciputri; Sheena Ramadhia Asmaradhani (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Premarital sexual behavior among adolescents remains a public health problem because it can lead to the risk of unwanted pregnancy, sexually transmitted diseases, and psychological impacts. Lack of knowledge about reproductive health is one of the factors causing the emergence of this risky behavior. This study aimed to analyze changes in adolescents' premarital sexual attitudes after reproductive health counseling. The research design used a pre-experimental with a one-group pre-test and post-test method. The research subjects were 70 eighth-grade students selected using a purposive sampling technique. The research instrument was a 23-item Likert scale questionnaire that had been tested for validity and reliability (Cronbach Alpha = 0.852). Data analysis included univariate and bivariate analysis using the Wilcoxon test because the data were not normally distributed. The results showed an increase in attitude scores after counseling, with an average pre-test score of 58.54 and a post-test score of 83.06. The median value increased from 53.50 to 84.00, while the mode increased from 77 to 92. The Wilcoxon test results showed a p-value < 0.05, which means there is a significant difference between the scores before and after counseling. In conclusion, reproductive health counseling has been proven to be effective in increasing